2020
DOI: 10.1128/mbio.03050-19
|View full text |Cite
|
Sign up to set email alerts
|

Robustness in an Ultrasensitive Motor

Abstract: In Escherichia coli, the chemotaxis response regulator CheY-P binds to FliM, a component of the switch complex at the base of the bacterial flagellar motor, to modulate the direction of motor rotation. The bacterial flagellar motor is ultrasensitive to the concentration of unbound CheY-P in the cytoplasm. CheY-P binds to FliM molecules both in the cytoplasm and on the motor. As the concentration of FliM unavoidably varies from cell to cell, leading to a variation of unbound CheY-P concentration in the cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(40 reference statements)
0
6
0
1
Order By: Relevance
“…A fraction of the data is shown in Figure 3B and in Appendix 1—figure 1 . This suggested that the default direction of flagellar rotation is CCW, similar to E. coli ( Ford et al, 2018 ; Liu et al, 2020 ). Considering that the bias is zero in the absence and ~0.35 in the presence of CheY, CheY-P binding likely promotes CW rotation in an otherwise CCW rotating motor in H. pylori .…”
Section: Resultsmentioning
confidence: 96%
“…A fraction of the data is shown in Figure 3B and in Appendix 1—figure 1 . This suggested that the default direction of flagellar rotation is CCW, similar to E. coli ( Ford et al, 2018 ; Liu et al, 2020 ). Considering that the bias is zero in the absence and ~0.35 in the presence of CheY, CheY-P binding likely promotes CW rotation in an otherwise CCW rotating motor in H. pylori .…”
Section: Resultsmentioning
confidence: 96%
“…After removal of metformin, the motor CW bias decreased to the pre-stimulus level rapidly. The chemotaxis system of E. coli is a robust adaptive system which allows the bacteria to sense and respond rapidly to the changes in the environment ( Alon et al, 1999 ; Liu G. et al, 2020 ). The motor CW bias was recovered to the initial level after rapid adaptation to the external attractant or repellent.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate that metformin prolonged the chemotactic recovery time of E. coli to the attractant. Previous findings revealed that the chemotaxis adaptation of E. coli to the attractant was ultrasensitive, wide-ranged, and robust ( Alon et al, 1999 ; Mello and Tu, 2007 ; Liu G. et al, 2020 ). In this study, we showed that the chemotactic response of wild-type cells for chemotaxis cultured in metformin to the attractant was different from cells cultured without metformin, in spite of the overall tendency of chemotactic response being similar.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial flagellar motor is ultrasensitive to the free CheY-P in the cytoplasm [ 49 , 50 , 51 ]. Without question, any slight change of the binding affinity of CheY for FliM will significantly affect the function of CheY in controlling flagellar motor.…”
Section: Discussionmentioning
confidence: 99%